Traidores a todos - Scerbanenco, Giorgio, 1911-1969; Weller, Cuqui; Scerbanenco, Giorgio, 1911-1969.; Akal Editor (Tres Cantos, Madrid, España : Ediciones Akal, S.A., 2009)
A lawyer who has spent time in prison with Duca is found drowned in one of the Milanese canals. Duca is contacted by a friend of the dead lawyer to perform surgery on a woman who after the operation confesses that although she is due to marry a wealthy butcher, is really in love with another man, the friend of the lawyer. Shortly afterwards, she is killed together with her lover. Duca discovers that the two events are linked and starts to unravel an arms and drugs trafficking business, centered in an understated trattoria, of which the two were part.
Online resource; title from ePub title page (Digitalia, viewed January 11, 2017)
Keywords: Murder -- Fiction; Betrayal -- Fiction; Noir fiction; Detective and mystery fiction; Electronic books